Group portrait of the attendees of the 1953 Monte Toyon I Camp - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the Monte Toyon I Camp, held August 22-29, 1953 in Aptos, California. A group of attendees can be seen holding a large banner that reads in part: "Lodo Centennial."